In-Situ Synchrotron X-ray Characterization of Corrosion Products in Zr Artificial Pits in Simulated Physiological Solutions. Issue 14 (1st January 2017) - Zhang, Yue; Addison, Owen; Gostin, Petre Flaviu; Morrell, Alexander; Cook, Angus J. M. C.; Liens, Alethea; Wu, Jing; Ignatyev, Konstantin; Stoica, Mihai; Davenport, Alison
Abstract : Corrosion products generated in artificial pits of zirconium were characterized in–situ by synchrotron X-ray diffraction and X-ray absorption near edge structure (XANES) in physiological saline, with and without addition of 4% albumin and/or 0.1% H2 O2 . Zr metal fragments and tetragonal ZrO2 particles were detected in aggregated black corrosion products away from the corrosion front. At the corrosion front, a ZrOCl2 ⋅8H2 O salt layer of a few hundreds of microns thickness was formed. Coarsened ZrOCl2 ⋅8H2 O crystallites were found farther out into the solution. The Zr solution species were confirmed to be in a tetravalent state by XANES. TEM imaging of the corrosion products revealed heterogeneity of the morphology of the Zr metal fragments and confirmed their size to be less than a few microns. The formation and speciation of Zr corrosion products were found not affected by the presence of H2 O2 and/or albumin in physiological saline. Furthermore, bulk Zr electrochemistry identified that the presence of H2 O2 and/or albumin did not affect passive current densities and pitting potentials of the bulk Zr surface. Therefore, it is concluded that the pitting susceptibility and pit chemistry of Zr in physiological saline were unaffected by the presence of H2 O2, albumin or their combinations.